ARCHAISMS IN THE ENGLISH LANGUAGE - Abdurahmonova Hayitgul,; Egamberdiyeva Hadicha, (TADQIQOTLAR, 2026)
Introduction Language  is  constantly  changing  and  evolving.  Over  time,  new  words  are created, while some old words gradually disappear from everyday use. These outdated or  old-fashioned  words  are  called  archaisms.  Archaisms  play  an  important  role  in understanding  the  historical  development  of  language  and  literature.  They  allow linguists, students, and researchers to study how language has evolved over centuries. Although archaisms are rarely used in modern everyday speech, they still appear in literature, religious texts, historical writing, and poetry. Understanding archaisms helps learners appreciate classical works and understand the cultural background of earlier periods. Language  is  constantly  changing  and  evolving.  Over  time,  new  words  are created, while some old words gradually disappear from everyday use. These outdated or  old-fashioned  words  are  called  archaisms.  Archaisms  play  an  important  role  in understanding  the  historical  development  of  language  and  literature.  They  allow linguists, students, and researchers to study how language has evolved over centuries. Although archaisms are rarely used in modern everyday speech, they still appear in literature, religious texts, historical writing, and poetry. Understanding archaisms helps learners appreciate classical works and understand the cultural background of earlier periods.